Job satisfaction and turnover intertion influence of organization performance: experience at higher education institution in Shanghai, China - Jusoh, Rosnani; Yue, Wang (Journal of Education and Social Sciences (JESOC), 2019)
As a powerful supplement to public higher education institution (HEI), private higher education plays an active role in popularizing the higher education to the massive number of students in China. This study explored the key relationship between job satisfaction and turnover intention among private HEI in Shanghai. 36-items from Job Satisfaction Survey (JSS) and 6-items from Turnover Intention Scale (TIS-6) were utilized to measure the level of job satisfaction and turnover intention respectively. Through stratified random sampling, 5 private HEI in Shanghai, China was selected with 212 lecturers involved in this study. The level of job satisfaction was at a moderate level (3.199 ± 0.906) and turnover intention was at a high level (4.258 ± 1.256). While these lecturers came from different backgrounds, there was no significant difference between male and female on the level of job satisfaction and turnover intention. There was a significant effect of highest qualification of lecturers on the level of job satisfaction and turnover intention. Job position of lecturers had a significant effect on several dimensions of job satisfaction. A significant negative correlation was found between the dimensions of job satisfaction and turnover intention. Multiple regression analysis further pin-points the exact impact of each dimension of job satisfaction, namely pay, promotion, operating procedure, and communication. This study recommended improvement in the pay level, effective incentive mechanism, fair promotion, solid professional development and rational operating procedure as an intervention to curb turnover intention.